Contemporary Legal Certainty in Insurance Default Claims: A Comparative Study of Islamic and Positive Law Perspectives - Isdiana Syafitri; Sunarmi; Kamello, Tan; Purba, Hasim (MILRev: Metro Islamic Law Review, 2025)
The breach of contract (wanprestasi) in contemporary insurance practices often results in legal uncertainty, particularly for insured parties who experience losses due to denied or inadequately fulfilled claims. This article examines the legal challenges associated with breach of contract claims in the Indonesian insurance context through a comparative analysis of positive and Islamic law perspectives. Utilizing a normative juridical approach, the study analyzes relevant legislation, including the Indonesian Civil Code (KUHPer) and Financial Services Authority (OJK) regulations, alongside principles of fiqh muamalah related to contracts, justice, and legal certainty. The findings reveal that while positive law offers a relatively structured legal framework, its practical implementation still encounters significant barriers to ensuring adequate legal protection. Conversely, Islamic law underscores the importance of contract clarity—particularly in tabarru' and tijarah agreements—and upholds justice as a core value in transactional relationships. These principles can enhance legal certainty and ethical standards in dispute resolution processes when applied. This article contributes to the academic discourse by providing a theoretical and comparative foundation for developing a more inclusive and justice-oriented insurance dispute resolution model that integrates national legal norms and Islamic ethical values. It is expected to offer valuable insights for policymakers, legal scholars, and practitioners in designing responsive insurance policies aligned with the needs of a pluralistic society.